2001
DOI: 10.1136/jcp.54.11.841
|View full text |Cite
|
Sign up to set email alerts
|

A pathological study of tumour regression in oesophageal adenocarcinoma treated with preoperative chemoradiotherapy

Abstract: Aims-To measure residual tumour in oesophageal adenocarcinoma treated with preoperative chemoradiotherapy, to correlate specific pathological variables with survival, and to describe morphological changes in tumour and non-neoplastic tissue resulting from preoperative treatment. Methods-Resection specimens from 47 cases of oesophageal adenocarcinoma treated with preoperative 5-fluorouracil/ cisplatin and radiotherapy were reviewed. Residual tumour was assessed in terms of tumour regression grade (TRG), pTNM st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…But this hypothesis was not confirmed by the analysis of Medich et al 7 There also is a relationship to be found between the prognosis and the lymph node status in the neoadjuvant treatment of organ tumors, as for instance in gastric carcinoma 35 or esophageal carcinoma 36 .…”
Section: Discussionmentioning
confidence: 92%
“…But this hypothesis was not confirmed by the analysis of Medich et al 7 There also is a relationship to be found between the prognosis and the lymph node status in the neoadjuvant treatment of organ tumors, as for instance in gastric carcinoma 35 or esophageal carcinoma 36 .…”
Section: Discussionmentioning
confidence: 92%
“…These changes generally represent a pattern of subacute inflammation, and in addition decreased tumor cell density, acellular mucus lakes, foamy histiocytes, fibrosis (especially in the submucosa and muscularis propria), dissolution of glands, giant cells, and cytological changes, such as apoptotic bodies and intracellular vacuoles. 8,12,16 Furthermore, tumor regression showed a centrifugal pattern with tumorfree fibrosis in the central and superficial, luminal portions of the tumor bed and residual tumor in deeper areas of the periphery; although tumor regression was associated with tumor downstaging of the ypT category in more than half of the patients, the remaining tumors with a partial regression (tumor regression grade 2) still had a ypT3 category. These findings confirm the need to work-up the whole tumor bed to detect scattered tumor residuals that are important for determining an accurate tumor category and regression classification.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Moreover, a high inter-observer reliability for those systems has been shown, with those systems equally applicable to both squamous cell carcinoma and adenocarcinoma. 21 After 15 years of diagnostic experience, we favor this scoring system in clinical practice over the widely used regression system described by Dunne et al 16 and Mandard et al, 22 which includes five tumor regression grades, based on the percentage of residual tumor in relation to therapy-induced fibrosis. A scoring system of three grades seems to be more easily implemented, more reproducible, and stronger and clearer with regard to prognostic impact.…”
Section: Discussionmentioning
confidence: 99%
“…A study that included 47 esophageal adenocarcinoma cases with preoperative therapy found that the involvement of local lymph nodes is the only relevant factor related to prognosis. 13 Retrospective analyses by Gu et al included 187 patients with adenocarcinoma in the lower esophagus or esophagogastric junction, all of whom received preoperative radiochemotherapy. In cases with more than two positive lymph nodes, the median survival time and overall survival are significantly lower than those with only one positive lymph node (47.1 months vs. 21.2 months, 34% vs. 6%, P = 0.02).…”
Section: Discussionmentioning
confidence: 99%